Transforming healthcare through just, equitable and quality driven artificial intelligence solutions in South Asia - Sushmita Adhikari; Iftikhar Ahmed; Deepak Bajracharya; Bishesh Khanal; Chandrasegarar Solomon; Kapila Jayaratne; Khondaker Abdullah Al Mamum; Muhammad Shamim Hayder Talukder; Sunila Shakya; Suresh Manandhar; Zahid Ali Memon; Moinul Haque Chowdhury; et al. (npj Digital Medicine)
Abstract AI can transform healthcare in LMICs by improving access, reducing costs, and enhancing efficiency. However, challenges such as safety, bias, and the resource constraints need to be addressed. Further, collaboration across domains is essential to develop capacity, user-friendly tools, and training. Ethical considerations should be central to AI deployment. By emphasizing gender equity, fairness, and responsible design, LMICs can harness AI’s power to enhance healthcare outcomes and advance equitable care.